Assessment of school energy efficiency using dynamic modeling when thermal protection requirements change - Deshko, V.; Bilous, I.; Holubenko, O. (Energy and Automation, 2023)
In this article, the authors conduct a comparative analysis of the impact of minimum insulation standards in accordance with DBN V.2.6-31:2016 and DBN V.2.6-31:2021 on the energy efficiency of school buildings. Using dynamic modeling and a non-steady-state energy model, the study confirms the advantages of new insulation standards that correspond to international and national energy efficiency standards. With the improvement of thermal protection according to DBN V.2.6-31:2016 and DBN V.2.6-31:2021, energy consumption decreases as follows: when improving walls to the level of DBN 2.6-31 2016 by 9.7 %, ceilings - by 10 %, windows - by 1.1 %, and the entire building envelope to the minimum requirements of 2.6-31 2016 by 20 %; when improving walls to the level of DBN 2.6-31 2021 by 9.8 %, ceilings - by 10.2 %, windows - by 1.8 %, and the entire building envelope to the minimum requirements of 2.6-31 2021 by 22.5 %. The results demonstrate the importance of understanding temperature dynamics, their impact on energy efficiency, and the need to study the interaction of various factors for developing optimal improvement strategies. Key words: thermal energy consumption, dynamic models, thermal insulation of buildings